Stress and marital adjustment in families of children with cancer. Issue 4 (1st March 2018) - Lavi, Iris; Fladeboe, Kaitlyn; King, Kevin; Kawamura, Joy; Friedman, Debra; Compas, Bruce; Breiger, David; Gurtovenko, Kyrill; Lengua, Liliana; Katz, Lynn Fainsilber
Abstract: Objective: Pediatric cancer is highly stressful for parents. The current prospective study examines the impact of several stressors (financial strain, life threat, treatment intensity, treatment‐related events, and negative life events) on the trajectory of marital adjustment across the first year following diagnosis. We examined whether average level of stressors across the year was related to (1) levels of marital adjustment at the end of the first year of treatment and (2 ) the rate of change in marital adjustment. Method: One hundred and thirty families of children newly diagnosed with cancer ( M age = 6.33 years, SD  = 3.61) participated. Primary caregivers provided 12 monthly reports on marital adjustment and stressors. Results: Multilevel models indicated that although marital adjustment was stable across the first year on average, random effect estimates suggested that this was the result of differing trajectories between families (eg, some increasing and others decreasing). Five individual stress constructs and a cumulative stress composite were then used to predict this variability. Higher average economic strain was related to consistently poorer marital adjustment across time. Higher average frequency of treatment‐related events and negative life events were associated with decreasing adjustment over time and lower adjustment at the end of the first year of treatment. Perception of life threat and treatment intensity were not associated with final levels or trajectory of adjustment. Finally, higher cumulative stress was associated with consistently poorer marital adjustment across time. Conclusion: Implications for identification of at‐risk families are discussed, and importance of delivering tailored interventions for this population.